The Referral System between Primary and Secondary Health Care in Saudi Arabia for Patients with Type 2 Diabetes: A Systematic Review - Mohammed Senitan; Ali Hassan Alhaiti; James Gillespie; Badar Faiz Alotaibi; George Binh Lenon (Journal of Diabetes Research)
Background. In Saudi Arabia, the mortality of diabetes is currently reported at 6%. A well-administered referral system is crucial in aiding the management of this disease. Method. A single reviewer employed a systematic approach to searching the literature databases with regard to the question: what are the attributes of referral systems in Saudi Arabia for patients with type 2 diabetes (T2D)? The results were analysed in order to provide recommendations to improve the Saudi health system. Results. Twelve primary studies were identified from a systematic search. Overall, the 12 studies did not clearly mention any of the factors of a good referral system. The referral problems identified by this study included patients’ unnecessary requests for referral, unstructured referral letters, and unclear dissemination guidelines for referral. Conclusions. This research attempted to identify the efficiency of the referral processes that were implemented for patients with T2D. The majority of the included studies were completely silent on the main referral factors for patients. If this review is representative of the referral system in Saudi Arabia, then, in the context of T2D, current referrals are unsafe. Further research on the quality of the referral system, taking into account at least some of the WHO referral guidelines, is required.